Síntese de hidroxiuretanas livres de isocianato via fixação de co2 - Bearzi, Jefferson Rotter (2021)
In order to seek alternative ways to mitigate the environmental impacts generated by CO2 emissions, one of the solutions is to develop processes that use this gas as raw material, enabling physical, chemical and biochemical routes in industrial processes. The conventional polycarbonate synthesis process involves the condensation of highly toxic phosgene and aromatic bisphenol. A replacement for phosgene in the synthesis of polycarbonates is the use of CO2 and epoxy, which allows a production process with less environmental impact, being possible to use these polycarbonates together with amines, providing the generation of urethanes without the use of isocyanates, known as Non-Isocyanate Urethanes (NIU's). The physicochemical properties acquired by NIU's can be modified based on the structures of their synthetic precursors, being possible to change and adjust properties such as elastic modulus, stiffness, thermal and oxidative stability, surface tension, resistance to abrasion and chemical products. The present work developed two cyclocarbonate precursors (mono and tris(cyclocarbonate) derived from commercial epoxy, which could be polymerized with aminosilane and primary aliphatic amines to obtain urethane polymers capable of forming films on vitreous, metallic and polymeric surfaces. Reactional progress of urethane and cyclocarbonate formation was followed by infrared spectroscopy (FTIR), where carbonyl bands of these products were observed at ~1800 cm-1 and ~1706 cm-1, respectively. Nuclear Magnetic Resonance (NMR) proved the formation of the precursor, presenting characteristic signals at [delta] =155.27 ppm (13C NMR) and between 4.40 and 4.80 ppm (1H NMR). The structural elucidation was also performed by Photoelectron Spectroscopy (XPS) observing the peak at 289.7 eV of the carbon resulting from urethane species (-NH-C*-OO). Subsequently, composite films of hydroxyurethanes were produced with different amounts of graphene and tested its cytotoxicity against osteoblast cells. The films did not cause a reduction greater than 30% in cell viability, indicating a biocompatible material.